Managing nature-based solutions in fire-prone ecosystems: Competing management objectives in California forests evaluated at a landscape scale - Herbert, Claudia; Haya, Barbara K.; Stephens, Scott L.; Butsic, Van (Frontiers in Forests and Global Change, 2022)
California’s cap-and-trade compliance offset market incentivizes forest managers to maintain elevated carbon stocks. It provides these incentives without enforcing standardized fire mitigation practices despite many projects being located in fire prone regions. Here, we evaluated the difference between management actions in California forests that participated in the carbon offset market versus those that engaged with state programs to reduce wildfire risk via fuel reduction treatments. Using remotely sensed data from the California Forest Observatory and the Moderate Resolution Imaging Spectroradiometer, we compared the vertical forest structure and vegetation canopy trends on forest offsets with forests that are receiving fuel treatment. We found California forests managed for carbon under the Improved Forest Management (IFM) program by the California Air Resources Board had higher levels of biomass than forests managed for fire risk reduction as indicated by 2016 lidar-estimated fuel loads. In addition, IFM-participating forests did not reduce their fuel loads between 2016 and 2020, whereas lands receiving grants for fuel management did, indicating that on average, the IFM projects were not engaging in fuel reduction efforts. However, despite the differences in fuel management between IFM projects and active fuel treatments, we found that both types of management saw a declining trend in vegetation greenness between 2015 and 2021. While declining greenness is expected of active fuel treatments associated with vegetation removal, such a trend in the case of IFM indicates additional wildfire risk. Managing forests for long-term carbon storage and sequestration requires consideration of fire risk mitigation. Given the little evidence of fuel reduction in the first decade of IFM projects implementation we question whether the century-long duration of carbon stocks in these offsets is realistic. We recommend that policymakers reevaluate the incentives directed at carbon stock preservation or expansion to better encompass the growing wildfire risk in California.